Epidemiology of Staphylococcus aureus bacteraemia at a tertiary children's hospital in Cape Town, South Africa - Naidoo , Reené (Department of Paediatrics and Child Health, 2025)
Background: Staphylococcus aureus is an important pathogen in paediatric patients with bloodstream infections. The epidemiology of S. aureus bacteraemia (SAB), however, has not been well documented in children in South Africa. Methods: A retrospective study was conducted at a children's hospital in Cape Town, South Africa, to investigate the epidemiology of SAB from 2007-2011. The incidence, clinical presentation, risk factors, management and outcomes of methicillin sensitive S. aureus (MSSA) and methicillin resistant S. aureus (MRSA) bacteraemia were compared. Results: Over the five year study period, 365 episodes of SAB were identified. The annual incidence of SAB was 3.28 cases per 1000 hospital admissions. MRSA was responsible for 26% of SAB and 72% of nosocomial infections. Only six possible cases of community-acquired MRSA infections were described. MSSA bacteraemia was more likely to present as pulmonary and bone or joint infections, while bacteraemia without a source was the most common presentation with MRSA. Infants, children with malnutrition, and residents of long-term care facilities were at highest risk for MRSA bacteraemia. The overall case fatality rate for SAB was 8.8% over five years, with MRSA being the only significant risk factor for mortality. Conclusion: The incidence of SAB and MRSA bacteraemia in children has remained stable over the past five years. MRSA is a predominantly nosocomial pathogen in children with SAB in Cape Town, South Africa